Individually tuned theta HD-tACS improves spatial performance - Da-Wei Zhang; Alexandros Moraidis; Torkel Klingberg (Brain Stimulation, 2022)
Background: Using transcranial alternating current stimulation (tACS) to improve visuospatial working memory (vsWM) has received considerable attention over the past few years. However, fundamental issues remain, such as the optimal frequency, the generality of behavioral effects, and the anatomical specificity of stimulation. Objectives: Here we examined the effects of two theory-driven tACS protocols for improving vsWM on behavioral and electroencephalogram (EEG) measures. Methods: Twenty adults each completed 3 HD-tACS conditions (Tuned, Slow, and Sham) on two separate days. The Tuned condition refers to a situation in which the frequency of tACS is tuned to individual theta peak measured during a vsWM task. By contrast, the frequency was fixed to 4 Hz in the Slow condition. A high-definition tACS was deployed to target smaller frontal and parietal regions for increasing their phase-locking values. During each tACS condition, participants performed vsWM, mental rotation (MR), and arithmetic tasks. Resting-state EEG (rs-EEG) was recorded before and after each condition. Results: Compared with Sham, Tuned but not Slow improved both vsWM and MR but not arithmetics. The rs-EEG recording showed an increased fronto-parietal synchrony for Tuned, and this increase in synchronicity was correlated with the behavioral improvement. A follow-up study showed no behavioral improvement in Tuned with an anti-phase setting. Conclusion: We provide the first evidence that simulating right fronto-parietal network with the tuned frequency increases the interregional synchronicity and improves performance on two spatial tasks. The results provide insight into the structure of spatial abilities as well as suggestions for stimulating the fronto-parietal network.